Scale up study of salt added batch distillation of azeotropic mixture : isopropanol/water - Jie, Liew Kok (2013)
Solvent recovery is often practised in chemical industry especially in glove and catheter manufacturing. However, azeotropic behaviour in mixture (isopropanol-water binary mixture) complicates the separation process. Conventional batch distillation is no longer effective in recovering the solvent. Moreover, the unrecovered solvent will end up as toxic waste and disposal of such toxic waste is jeopardising to the environment. Experimental works were carried out and scaling up study was performed in order to solve these problems. The research objectives are twofold: (a) to determine optimum salt concentration for distilling IPA-water azeotropic mixture by using salt added batch distillation to recover IPA for purity more than 90 mol%, and (b) to study scaling up of salt added batch distillation unit for IPA-water azeotropic mixture from a laboratory scale to pilot plant scale. Two stages of procedures, which are laboratory scale and pilot plant experiments, were carried out. The optimum salt concentration and the scaling up were studied. The optimum salt concentration needed to break the azeotropic point of IPA-water mixture is generally decreasing as z1 is higher. Salt solution was dissolved to the still before distillation using laboratory scale and no reflux ratio can be controlled due to simpler apparatus. Results showed that 2.5 mol% and 1.57 mol% of calcium chloride salt has successfully recover 91 mol% of IPA from a IPA-water system with z1 = 0.51 and 0.60, respectively. The binary mixture azeotropic point is successfully broken down by calcium chloride salt addition. In pilot plant, salt solution was added near to the top of column and total reflux ratio was applied to enhance mass and heat transfer in salt effect distillation. However, it did not succeeded in recovering high purity of IPA, probably due to errors in the extension of binary data to multi-component systems.